Current status and progress on the application of key stratum theory in mining subsidence - Chen Chao; Hu Zhenqi (矿业科学学报, 2017)
The generation background, development process and application status of the key stratum(KS) theory were described, then the necessity of the application of KS theory in mining subsidence was analyzed.The Current status and progress on the application of KS theory in mining subsidence, such as the impact of KS on surface subsidence, subsidence prediction, mining-induced crack, surface subsidence reduction and goaf stability, were introduced in detail.The analysis indicates that it is helpful to study on dynamic process of surface subsidence formation mechanism of mining-induced crack, the accuracy of subsidence prediction and surface subsidence reduction effects may be improved in the application of KS theory in mining subsidence.The limitations of present literature were investigated, and the areas for further study in the future were proposed.